A case of Citizen Science for Cell Biology Images Analysis - Lanza, Eduardo Lostal; Sanz, Fermín Serrano; Val Gascón, Carlos; Garcia, Francisco Sanz; Alonso, Patricia Martínez; Villar, J. A. Carrodeguas (Anais do Brazilian e-Science Workshop (BreSci); 2013: Anais do VII Brazilian e-Science Workshop, 2013)
As a consequence of the quick advance in technology, people is more connected than ever. Researchers can take advantage of this fact to overcome problems, that some of them are facing and have become their bottleneck. Infeasibility for processing vast amount of information or the need for a wider range of inputs are some of those problems. Citizen science seems to be a proper approach to overcome them at the same time that make general public participant of the science process. A complete scenario in cell biology research field is presented where cell images analysis is carried out through crowdsourcing.